2018
DOI: 10.1111/nph.15338
|View full text |Cite
|
Sign up to set email alerts
|

Small‐scale indirect plant responses to insect herbivory could have major impacts on canopy photosynthesis and isoprene emission

Abstract: Insect herbivores cause substantial changes in the leaves they attack, but their effects on the ecophysiology of neighbouring, nondamaged leaves have never been quantified in natural canopies. We studied how winter moth (Operophtera brumata), a common herbivore in temperate forests, affects the photosynthetic and isoprene emission rates of its host plant, the pedunculate oak (Quercus robur). Through a manipulative experiment, we measured leaves on shoots damaged by caterpillars or mechanically by cutting, or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 98 publications
(151 reference statements)
2
35
0
1
Order By: Relevance
“…Although herbivory was generally low, values were within the range registered by other studies in grasslands (e.g., Scherber et al 2006) and were in agreement with the patterns observed in recent reviews of insect herbivory (Zhang et al 2016, Kozlov andZvereva 2018). It has been observed that even low levels of leaf area removed can trigger alterations in plant physiology and nutritional quality (Kerchev et al 2012, Visakorpi et al 2018) and in turn affect plant population dynamics (Stein et al 2010, Allan andCrawley 2011).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although herbivory was generally low, values were within the range registered by other studies in grasslands (e.g., Scherber et al 2006) and were in agreement with the patterns observed in recent reviews of insect herbivory (Zhang et al 2016, Kozlov andZvereva 2018). It has been observed that even low levels of leaf area removed can trigger alterations in plant physiology and nutritional quality (Kerchev et al 2012, Visakorpi et al 2018) and in turn affect plant population dynamics (Stein et al 2010, Allan andCrawley 2011).…”
Section: Discussionsupporting
confidence: 89%
“…, Visakorpi et al. ) and in turn affect plant population dynamics (Stein et al. , Allan and Crawley ).…”
Section: Discussionmentioning
confidence: 99%
“…FORCAsT employs a half‐hourly timestep. Our simulations therefore focused on the emissions of isoprene, which are calculated in FORCAsT by summing the contributions from 10 leaf angle classes in each crown‐space model level, following the algorithms of Guenther et al ():ER=LAI·ε·γiso,where ER is the total emission rate (mg m −2 hr −1 ), LAI (m 2 /m 2 ) is the leaf area index and ε is a site‐ and species‐specific emission factor (1.20 mg m −2 hr −1 for Q. robur ; Visakorpi et al, ) which represents the emission rate of isoprene into the canopy at standard conditions of 30°C and 1,000 µmol m −2 s −1 . LAI was taken as the maximum reported for the site (3.6 m 2 /m 2 ; Herbst, Rosier, Morecroft, & Gowing, ) throughout this study which coincides with the period of peak growth.…”
Section: Methodsmentioning
confidence: 99%
“…The simulated exchange of heat and trace gases is further improved by constraining the friction velocity (u*) and the standard deviation of the vertical wind component (σ w ) following Bryan et al (2012). As u* and σ w were not measured at Wytham, we estimated each from the horizontal wind speed (u) following Makar et al (2017), Equation (1), and Shuttleworth and Wallace (1985), Equation (2) where ER is the total emission rate (mg m −2 hr −1 ), LAI (m 2 /m 2 ) is the leaf area index and ε is a site-and species-specific emission factor (1.20 mg m −2 hr −1 for Q. robur; Visakorpi et al, 2018) which represents the emission rate of isoprene into the canopy at standard conditions of 30°C and 1,000 µmol m −2 s −1 . LAI was taken as the maximum reported for the site (3.6 m 2 /m 2 ; Herbst, Rosier, Morecroft, & Gowing, 2008) throughout this study which coincides with the period of peak growth.…”
Section: Model Descriptionmentioning
confidence: 99%
“…785–798). Finally, Visakorpi et al . (in this issue, pp. 799–810), found that herbivory reduced photosynthesis dramatically across a whole canopy level and increased isoprene emission.…”
mentioning
confidence: 96%